Microsoft SharePoint Server 2010 (Capacity planning for Microsoft SharePoint Server 2010) (Microsoft Press, 2015)
This book provides information about planning for capacity and performance requirements for deploying Microsoft SharePoint Server 2010. Subjects include sizing, performance testing, software boundaries, and capacity case studies. The audiences for this book are business application specialists, line-ofbusiness specialists, information architects, IT generalists, program managers, and infrastructure specialists who are planning a solution based on SharePoint Server 2010. This book is part of a set of four planning guides that provide comprehensive IT planning information for SharePoint Server...